Synthesis of TiO₂/Hydroxyapatite Composite Based on Chicken Egg Shells for Methylene Blue Photodegradation - Dhea Annisa Zein; F. Widhi Mahatmanti; Sri Wahyuni; Nuni Widiarti (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Hydroxyapatite (HAp) was synthesized using low-cost eggshell waste and employed as a composite support material for a TiO2 photocatalyst. The TiO2/HAp composite was characterized using X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, and a surface area analyzer (SAA). XRD analysis confirmed the presence of TiO2/HAp, revealing a crystallite size of 9.42 nm. The FTIR spectra further verified the characteristic peaks of TiO2/HAp, corresponding to those of TiO2 and HAp. BET-BJH analysis indicated that the surface area followed the trend TiO2 > TiO2/HAp > HAp trend, while the pore volume and diameter followed the HAp > TiO2 > TiO2/HAp. The photocatalytic activity of TiO2/HAp in methylene blue degradation was evaluated using a UV-Vis spectrophotometer, demonstrating excellent performance. The TiO2/HAp composite achieved a 99.10% photodegradation of 20 ppm methylene blue within 120 minutes, with an adsorption capacity of 8.3078 mg/g. The photodegradation efficiency for 40 ppm methylene blue was 86.47%, with an adsorption capacity of 13.6335 mg/g. These results confirm that HAp effectively inhibits the electron recombination process in TiO2, thereby enhancing its photocatalytic performance. This study highlights the potential of HAp for developing cost-effective and high-efficiency TiO2-based photocatalysts, offering a sustainable and environmentally friendly approach to water purification.